Model of Fiscal Sustainability of Enterprise - Aristarkhova, Margarita Konstantinovna; Zueva, Olga Konstantinovna; Zueva, Maria Sergeevna (Economy of Regions, 2018)
The paper substantiates the possibility and the necessity to introduce the notion of «fiscal sustainability». Fiscal sustainability is the company's ability to meet its tax obligations and to function normally according to its tasks, despite the influence of economic changes in external and internal environment. The investigation of the introduced category allowed making the following conclusions. Firstly, fiscal sustainability and financial sustainability are interdependent. Secondly, we defined the exogeneous and endogenous factors, which cause changements in the state of fiscal sustainability and predetermine its «contraction» and «expansion». Thirdly, the category of fiscal sustainability has local and global characteristics. And last, fiscal sustainability needs temporal characteristics: operational, tactical, and strategic ones, and quantitative representation. We propose the indicators for assessing the fiscal sustainability of an enterprise. The quantitative assessment of fiscal sustainability can be represented by the following indicators: the coverage ratio of tax payments; structural ratio of tax debt and paid tax payments; as well as the rate of tax debt growth. We present models for calculating these indicators values, and substantiate the possibility of their performance management. We assess planned and actual values for fiscal sustainability on the basis of the developed system of indicators, and then level the resulting deviations. This task is of a complex nature, covering all phases of the management of. Fiscal sustainability can be measured for different time periods. Therefore, the system of fiscal sustainability management refers to strategic, tactical and operational levels. The application of the research results will provide to the enterprises an opportunity to meet their tax obligations.